Louis MacNeice and the Irish poetry of his time - Walker, Tom 1981- (Oxford Univ. Press, 2015)
This study focuses on Louis MacNeice's creative and critical engagement with other Irish poets during his lifetime. It draws on extensive archival research to uncover the previously unrecognised extent of the poet's contact with Irish literary mores and networks. Poetic dialogues with contemporaries including F.R. Higgins, John Hewitt, W.R. Rodgers, Austin Clarke, Patrick Kavanagh, John Montague, and Richard Murphy are traced against the persistent rhetoric of cultural and geographical attachment at large in Irish poetry and criticism during the period. These comparative readings are framed by accounts of MacNeice's complex relationship with the oeuvre of W.B. Yeats, which forms a meta-narrative to MacNeice's broader engagement with Irish poetry. Yeats is shown to have been MacNeice's contemporary in the 1930s, reading and reacting to the younger poet's work, just as MacNeice read and reacted to the older poet's work. But the ongoing challenge of the intellectual and formal complexity of Yeats's poetry also provided a means through which MacNeice, across his whole career, dialectically developed various modes through which to confront modernity's cultural, political and philosophical challenges. This book offers new and revisionary perspectives on MacNeice's work and its relationship to Ireland's literary traditions, as well as making an innovative contribution to the history of Irish literature and anglophone poetry in the twentieth century